Being Selective and Communicative in Choosing a Partner as the Foundation of a Harmonious Family - Adila Syaidatun Nisa; Luthfan Tri Mukti; Frian Wisesa; Humaeroh Humaeroh (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Choosing a life partner is a fundamental step in building a harmonious and lasting family. In modern society, the increasing number of domestic conflicts and divorces reflects the importance of individual readiness in selecting the right partner. Therefore, being selective and communicative are essential considerations in the partner-selection process. This study aims to examine the role of selective and communicative attitudes as a foundation for forming a harmonious family. The method used is a literature review with a descriptive-analytical approach, drawing on data from books, academic journals, and other relevant scholarly sources on interpersonal and family relationships. The findings reveal that a selective approach enables individuals to evaluate compatibility in terms of values, character, background, and emotional and social readiness, thereby reducing the risk of future conflicts. Meanwhile, a communicative approach characterized by openness, honesty, and mutual understanding plays a vital role in building trust, strengthening emotional connections, and resolving conflicts constructively. Effective communication also helps partners understand each other more deeply, anticipate potential problems, and identify appropriate solutions. Thus, the integration of selective and communicative attitudes becomes a key foundation for achieving a stable, harmonious, and sustainable family life.